The Influence of Knowledge, Attitude, Family Support and Peer Support on The Behavior of Female Teenage Menstrual Hygiene - Ningrum, Meika Ayu Cahya; Indriyanti, Dyah Rini (Universitas Negeri Semarang, 2018)
__________________________________________________________Teens who have experienced menarche become more susceptible to reproductive health problems such as Reproductive Tract Infection, especially Indonesian women because it triggers hot and humid air. In the year 2015 in Jombang district which experienced an increase in number of people with Reproductive Tract Infection (RTI) such as candidiasis 5.50% from the previous year. Hygiene behavior during menstruation is important in determining the health of reproductive organs.The purpose of this research was to analyze the influence of knowledge, attitude, family support and peer support on the behavior of female teenage menstrual hygiene.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â The sttudy design used analytic with cross sectional approach through survey method. The population was all of female students of grade VIII SMP Negeri 1 Mojowarno who has experienced menstruation amounted to 198 female studentss. The samples were 68 respondents with simple random sampling technique. Chi-Square test results show that there is significantan effectÃ‚Â of knowledge on the behavior of menstrual hygiene (p = 0,000); there is significantan effectÃ‚Â of attitude on behavior of menstrual hygiene (p = 0.000); there is significantan effect of family support on the behavior of menstrual hygiene (p = 0,000); there is significantan effect of peer support on the behavior of menstrual hygiene (p = 0.018). Logistic regression test results show that more dominant knowledge affecting behavior of menstrual hygiene p = 0,011 and value of OR 8,645. The conclusions of knowledge, attitude, peer support and family support have an effect on the behavior of menstrual hygiene. This research is expected as an input to make development planning of YCCS (Youth Care Care Service) so that adolescent can apply good menstrual hygiene